Damage to The Surface Of Children's Teeth Due To The Impact Of Milk Formula Giving Patterns Over A Long Period Of Time Due To Acid Production In The Oral Cavity (Caries) - Musaidah, Musaidah; Simanjuntak, Glory Gelarich; Rahmat, Rezqiqah Aulia; P, Nur Triningtias (International Journal of Health Sciences, 2025)
Formula milk is milk produced by industry. For needs intake nutrition in the system body child which contain carbohydrate like sucrose and lactose which can result in caries teeth in children age preschool. Dental caries is one of disturbance health teeth that experience calcification so that tooth become porous, perforated even broken. Research Objectives this is for know influence consumption of formula milk against caries teeth. Research this use type study literature study, where method literature study looking for data used originate from textbooks, journals, articles scientific, literature review containing about Influence Consumption Formula Milk Against Caries Teeth. Research results that consumption of formula milk has an effect to caries tooth child age preschool. Content carbohydrate like sucrose and lactose can cause caries teeth and if too often consuming formula milk then level severity caries tooth the more high. Research conclusion this is factor main the occurrence caries in children age preschool is with consume food and drink cariogenic.